2007
DOI: 10.1177/021849230701500609
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation for Prosthetic Heart Valves in Pregnancy. Is There an Answer?

Abstract: The aim of this retrospective study was to compare the different anticoagulation regimens used in pregnant women with prosthetic heart valves. We reviewed 196 pregnancies in 110 women from 1974 to 2000. The patients were divided into two groups: group 1 (142 pregnancies) had warfarin throughout pregnancy; and in group 2 (54 pregnancies), warfarin was replaced by subcutaneous heparin during the first trimester and last two weeks of pregnancy. There were no maternal complications in 129 pregnancies in group 1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 20 publications
3
46
0
Order By: Relevance
“…Eighteen studies, totaling 800 pregnancies between 1974 and 2014, were included in the final analysis 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33 (Table 1). Patients in 8 of the studies were followed prospectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighteen studies, totaling 800 pregnancies between 1974 and 2014, were included in the final analysis 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33 (Table 1). Patients in 8 of the studies were followed prospectively.…”
Section: Resultsmentioning
confidence: 99%
“…Spontaneous abortion was defined as any unplanned fetal loss before 20 weeks of gestation in 16 studies 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 22 weeks in 1 study (32), and 24 weeks in 1 study (33). Fetal death was defined as any unplanned fetal loss at or after 20 weeks of gestation in 16 studies 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 22 weeks in 1 study (32), and 24 weeks in 1 study (33). To avoid misclassification, we used the definition provided by each individual study.…”
Section: Methodsmentioning
confidence: 99%
“…49,50,[332][333][334][335][336][337][338][339][340] In a systematic review of observational studies between 1966 and 1997 that reported on outcomes with various anticoagulant regimens in pregnant women with mechanical prosthetic valves, the regimen associated with the lowest risk of valve thrombosis/systemic embolism was the use of vitamin K antagonists throughout pregnancy (3.9%). 49 The use of UFH in the fi rst trimester and near term was associated with a higher risk of valve thrombosis (9.2%).…”
Section: Anticoagulant Management Of Mechanical Prosthetic Valves In mentioning
confidence: 99%
“…49,50,[332][333][334][335][336] The number of pregnancy losses appears higher in those patients who receive either vitamin K antagonists or a heparin throughout pregnancy than in those in whom UFH or LMWH are substituted for vitamin K antagonists in the fi rst trimester and at term. 49,50,[332][333][334][335][336][337][338][339][340] Adjusted-dose bid LMWH throughout pregnancy, with doses adjusted to achieve the manufacturer's peak anti-Xa LMWH 4 h postsubcutaneous injection (Grade 1A). Adjusted-dose UFH throughout pregnancy administered subcutaneously every 12 h in doses adjusted to keep the midinterval aPTT at least twice control or attain an anti-Xa heparin level of 0.35-0.70 units/mL (Grade 1A).…”
Section: E725smentioning
confidence: 99%
“…14 This dose-dependent risk was replicated by Khamooshi et al 15 In a retrospective study of 196 pregnancies over 3 decades, they compared fetal and maternal complications among women with mechanical heart valves who used warfarin throughout pregnancy with women who substituted subcutaneous heparin during the first 12 weeks and last 2 weeks of pregnancy and found that women who achieved INR of 2.5 to 3.5 with ≤5 mg of warfarin daily had better maternal outcomes and less fetal loss than the heparin group. Continuation of warfarin during the first trimester is reasonable for pregnant women with a mechanical valve if the dose of warfarin to achieve a therapeutic INR is ≤5 mg (AHA/ACC Guidelines Class IIA recommendation).…”
Section: Dose-dependent Effectsmentioning
confidence: 86%